Modelo de ferramenta para avaliação e diagnóstico das organizações de aprendizagem - Hallgren, Nadir Ramos de Almeida (2003)
This work was elaborated from a bibliography review in which were extracted elements explored and used by the researcher in the context of a new perspective that served as base for the proposal of an integrated and ample pattern about learning organizations. With this new pattern the researcher elaborated a tool in order to use it as a reference for initiatives in companies, both for valuation or diagnosis and for implementation guide of this management pattern. The function of the mentioned pattern, which was called FADOA, is to become a great facilitator of practical and/or strategic use for companies and for people who study the theme, especially, because of its capacity to evidence a very synthetic and very simple classification index of the company development level from the complex universe of the learning organizations. Since the beginning of this work there was preoccupation about simplifying without reducing, in other words, to transform a complex thing in a simple one without promoting a linear and poor reduction, following the orientation of the anthropologist LÉVI-STRAUSS (1990) and always considering that the scientific explanation is not the way of the complex fact to the simple one, but the trail to make complexity more intelligible. The pattern was put into practice and it was successful at the company called Caterpillar do Brasil Ltda.